Ambient noise analysis on sound for use in wireless digital transmission - Kuruvilla, Mathew; Issac, Biju; Tan, Chong Eng (2013)
Ambient noise is present everywhere in varying degrees of frequencies and amplitudes. This paper tries to analyse the ambient noises in various environments ranging from quiet room to busy public places to remote jungle type locations in order to study the impact of noise while using sound as a low frequency wireless carrier for digital data. We try to find the suitable frequency band for text transmission using soundby identifyingthe sound spectrum band least susceptible to ambient noise and do some test communication.